e-Story in library - Md Rosli Shanarat, Nurul Elina; Mohd Nasharudin, Nazratul Aina; Mohamad Tanuri, Zati Atiqah (Universiti Teknologi MARA, Kedah, 2017)
Multimedia is the combination of text, graphics, sound, video and animation. Multimedia is now widely used in education, business, entertainment and even public facilities. Since multimedia is now broadly used in our country, the introduction of multimedia especially interactive multimedia to children is one of the best approaches to attract children to go to the library and expose them with the fun and excitement of multimedia. It can develop their cognitive, psychomotor, interpersonal and affective domains or skills. Therefore, multimedia helps to enhance their learning outcomes. Generally, this multimedia application consists of a few children’s stories in two different languages, English and Bahasa Malaysia. Moreover, the use of graphics in this multimedia application can improve their interest and make the children understand the stories better. Apart from that, the narration will assist the children in pronouncing the words correctly. This multimedia application helps children to develop their listening and reading skills. Indirectly, the introduction of multimedia application will encourage children to use the services and facilities in the library. Moreover, this application will change the reading habit from paper-based to digital version suitable with the latest advance of Information Technology.